2013
DOI: 10.1242/dmm.010710
|View full text |Cite
|
Sign up to set email alerts
|

Motor neurons and glia exhibit specific individualized responses to TDP-43 expression in a Drosophila model of amyotrophic lateral sclerosis

Abstract: SUMMARYAmyotrophic lateral sclerosis (ALS) is a fatal disease characterized by complex neuronal and glial phenotypes. Recently, RNA-based mechanisms have been linked to ALS via RNA-binding proteins such as TDP-43, which has been studied in vivo using models ranging from yeast to rodents. We have developed a Drosophila model of ALS based on TDP-43 that recapitulates several aspects of pathology, including motor neuron loss, locomotor dysfunction and reduced survival. Here we report the phenotypic consequences o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
92
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(106 citation statements)
references
References 59 publications
(100 reference statements)
13
92
1
Order By: Relevance
“…This is particularly true of most P-body and stress granule factors 10 (with exceptions e.g., Dcp2 in P-bodies). Germ granule components (e.g., Vasa in Drosophila nuage; residency time of 60s; 126 PGL-1 in C. elegans perinuclear P-granules 20s 21 ), and neuronal granule components (e.g., Staufen in Drosophila neuronal granules; residency > 10 min; 104 TDP-43 in Drosophila neuronal granules 10s 127 ) also exhibit a wide range of shuttling rates. More telling are FRAP studies on fluorescently labeled mRNAs, which have indicated that both rapidly exchanging and immobile fractions of a single mRNA species can exist within stress granules simultaneously.…”
Section: Role Of Mrnp Granules In Mrna Stabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly true of most P-body and stress granule factors 10 (with exceptions e.g., Dcp2 in P-bodies). Germ granule components (e.g., Vasa in Drosophila nuage; residency time of 60s; 126 PGL-1 in C. elegans perinuclear P-granules 20s 21 ), and neuronal granule components (e.g., Staufen in Drosophila neuronal granules; residency > 10 min; 104 TDP-43 in Drosophila neuronal granules 10s 127 ) also exhibit a wide range of shuttling rates. More telling are FRAP studies on fluorescently labeled mRNAs, which have indicated that both rapidly exchanging and immobile fractions of a single mRNA species can exist within stress granules simultaneously.…”
Section: Role Of Mrnp Granules In Mrna Stabilitymentioning
confidence: 99%
“…147 In addition, pathogenic forms of TDP-43 expressed in C. elegans or Drosophila show slower exchange rates from aggregates or neuronal granules by FRAP. 127,148 Several reasons have been proposed as to why persistent stress granules or related mRNP aggregates could be toxic to cells. 136,144 Sequestration of protein factors in granules could lead to a reduced ability of granules to appropriately remodel mRNPs, and may limit the available pool of a protein that also functions elsewhere in the cell.…”
Section: Toxic Stress Granules As a Cause Of Degenerativementioning
confidence: 99%
“…The authors suggested that changes in the Drosophila orthologues for EAAT1/EAAT2 which are involved in glutamate transport, might underlie the phenotype in both knockdown as well as overexpression models. Although motor neuron specific mTDP-43 expression in Drosophila seems to confer different effects on the cellular level as compared to mTDP-43 expression in glial cells, its effects on the phenotypical level is very similar (Estes et al, 2013). …”
Section: Glial Cells Contribute To Motor Neuron Degenerationmentioning
confidence: 99%
“…The results have shown that WT hTDP-43, as well as A315T, D169G, G298S and N345K mutants, mislocalize to the cytoplasm when overexpressed (Estes et al, 2013). WT and mutant hTDP-43 overexpression in both glial and motor neuron cells also reduces bouton number at larval NMJ’s and hinders larval motor function, specifically their ability to turn over after being flipped upside down.…”
Section: 0 Drosophila Models Of Alsmentioning
confidence: 99%